ANALYSIS OF THE FINANCIAL PERFORMANCE OF THE REGIONAL GOVERNMENT OF CENTRAL BENGKULU REGENCY WITH THE APPROACH OF THE PERFORMANCE MEASUREMENT - Ghia Amanda Riska Pabela; Fachruzzaman Fachruzzaman (Transpublika Publisher, 2025)
This study aims to analyze the financial performance of the regional government of Central Bengkulu Regency with a performance measurement system approach using financial ratio indicators, such as the effectiveness ratio, fiscal decentralization ratio, efficiency ratio, and growth ratio. This research uses a quantitative descriptive approach with secondary data in the form of the 2019-2023 Budget Realization Report. The data collection technique was carried out with a documentation study accessed from the official website of the DJPK (Directorate General of Fiscal Balance). The results showed that the average effectiveness ratio was classified as effective with a figure of 94.95%. In contrast, the fiscal decentralization ratio only reached an average of 3.30% with a very low category. On the other hand, the average fiscal decentralization ratio reached 3089.50%, indicating very high inefficiency. Meanwhile, the PAD growth ratio experienced fluctuations but in a positive direction.